Implementation of E-HRM (Electronic Human Resource Management) with Zoho Application: A Case Study - Krisnadinatha, I Gede Arya; Suarjaya, I Made Agus Dwi; Pratama, I Putu Agus Eka (JITTER : Jurnal Ilmiah Teknologi dan Komputer; Vol 4 No 3 (2023): JITTER, Vol.4, No.3 December 2023, 2024)
Electronic Human Resource Management (e-HRM) is an information system that handles problems related to human resource management in an organization (company). The problem raised in this research is the company's limitations in the management of existing Human Resources (HR), with a proposed solution in the form of an integrated Human Resource management information system. In implementing this e-HRM system using tools from a third party, namely Zoho, Zoho is a platform that allows HRD / Personnel to carry out human resource management starting with the recruitment or outsourcing process and continuing with the process of managing existing human resource data in the company. From the research that has been done, the results that the use of modules contained in Zoho can help companies company by 83.22% in conducting employee management.